The Self-Concept Of Young Married With Cage Friends - Okta Asmita; Sapta Sari; Sri Narti (Perkumpulan Dosen Muda (PDM) Bengkulu, 2021)
The phenomenon of early marriage is a problem that often occurs and is considered normal by adolescents in Central Bengkulu district which is included in the category of the top three cases of early marriage in Bengkulu province in 2019. The purpose of this study was to determine the self-concept of teenagers marrying young with peers in Kertapati village. Homecoming. This study uses descriptive qualitative research methods with data collection techniques through observation, interviews and documentation. The theory used is William Brooks (2017: 108), namely the factors that influence a person's self-concept. The results of the study show that the self-concept of adolescents who marry young with their peers is formed through their first view of themselves which assumes that they are ready to marry even though they are still young, this is evidenced by changes in attitudes that adjust their roles and status as married. Second, reactions and responses from other people can shape the self-concept of young married couples developing through the interaction of married couples with the community. The self-concept is formed from the learning process by understanding the reactions and responses of neighbors, village heads and BMA leaders so that married couples participate in socializing and participating in society. Third, the self-concept of young married couples formed from their roles as husband and wife in the household has an influence in the formation of a positive self-concept, this is also influenced by the role of parents, peers and the environment. So at first the self-concept of teenagers marrying young with peers is a negative self-concept, but it develops after marriage into a positive self-concept because they are able to solve their own problems and have participated in their environment.